A Fixed Point Approach to the Stability of the Functional Equation f(x+y)=F[f(x), f(y)]. (11th October 2009) - Jung, Soon-Mo; Min, Seungwook
Abstract : By applying the fixed point method, we will prove the Hyers-Ulam-Rassias stability of the functional equationf ( x + y ) = F [ f ( x ), f ( y ) ] under some additional assumptions on the functionF and spaces involved.